Gastrointestinal stromal tumors (GIST) - Varela, Daniel; Viola, Marcelo; Puñal, Alicia; Kenny, Juan; Zeballos, Justino (Cirugía del Uruguay, 2006)
The term gastointestinal stromal tumor (GIST) is used to detemine the most common type of mesenchymal tumor of the gastrointestinal tract; they are apt to appear anywhere within the gastrointestinal tract and at times in the mesente. This paper is an update of a topic of increasing interest in our scenaío and one that presents diículties as to diagnosis equiring immunohistochemical techniques to categorize it. Pogress as to its genetic data has rendered possible identiying a speciic molecular anomaly and, simultaneousl, the speciic drug for this anomaly. These tumors represent a paticular nosologic entit, as fom the discovey in 1998 of the manifestation of a mutated receptor of tirosinchinase (e-KIT) in the fusiform ce/Is of which they are composed. Notwithstanding speciiciy of CD 117 for the purpose of diagnosis, there st1 rema in a 1 % of these tumors, which are CD 117 negative, therefore in order to diagnose them morphologic identiication by an epert pahologist is required.